2020
DOI: 10.1016/j.bbmt.2020.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life following Allogeneic Stem Cell Transplantation for Patients Age >60 Years with Acute Myelogenous Leukemia

Abstract: This study of patients with acute myelogenous leukemia (AML) age 60 years analyzed the association between patients' performance indices-Hematopoietic Stem Cell Transplantation Comorbidity Index (HCT-CI), Karnofsky Performance Score (KPS), and European Society for Blood and Marrow Transplantation (EBMT) risk score-before undergoing allogeneic hematopoietic stem cell transplantation (allo-HSCT) and quality of life (QoL), quantified using the Functional Assessment of Cancer Therapy-Bone Marrow Transplant Scale (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 43 publications
2
0
0
Order By: Relevance
“…In the present study, after total therapy, more than 90% of long‐term survivors were reported with satisfactory recovery of HR‐QoL. The mean HR‐QoL scores were good and comparable with those reported in a previous study conducted on patients with AML in CR1 [37]. Pidala et al.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the present study, after total therapy, more than 90% of long‐term survivors were reported with satisfactory recovery of HR‐QoL. The mean HR‐QoL scores were good and comparable with those reported in a previous study conducted on patients with AML in CR1 [37]. Pidala et al.…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, after total therapy, more than 90% of long-term survivors were reported with satisfactory recovery of HR-QoL. The mean HR-QoL scores were good and comparable with those reported in a previous study conducted on patients with AML in CR1 [37]. Pidala et al [20] reported that, compared with that of patients with mild or moderate chronic GvHD, patients with severe chronic GvHD had the poorest recovery of HR-QoL.…”
Section: Discussionsupporting
confidence: 88%